Fecal Microbiotas of Indonesian and New Zealand Children Differ in Complexity and Bifidobacterial Taxa during the First Year of Life - Lawley, Blair (Appl Environ Microbiol, 2019)
The biological succession that occurs during the first year of life in the gut of infants in Western countries is broadly predictable in terms of the increasing complexity of the composition of microbiotas. Less information is available about microbiotas in Asian countries, where environmental, nutritional, and cultural influences may differentially affect the composition and development of the microbial community. We compared the fecal microbiotas of Indonesian (n = 204) and New Zealand (NZ) (n = 74) infants 6 to 7 months and 12 months of age. Comparisons were made by analysis of 16S rRNA gene sequences and derivation of community diversity metrics, relative abundances of bacterial families, enterotypes, and cooccurrence correlation networks. Abundances of Bifidobacterium longum subsp. infantis and B. longum subsp. longum were determined by quantitative PCR. All observations supported the view that the Indonesian and NZ infant microbiotas developed in complexity over time, but the changes were much greater for NZ infants. B. longum subsp. infantis dominated the microbiotas of Indonesian children, whereas B. longum subsp. longum was dominant in NZ children. Network analysis showed that the niche model (in which trophic adaptation results in preferential colonization) of the assemblage of microbiotas was supported in Indonesian infants, whereas the neutral (stochastic) model was supported by the development of the microbiotas of NZ infants. The results of the study show that the development of the fecal microbiota is not the same for infants in all countries, and they point to the necessity of obtaining a better understanding of the factors that control the colonization of the gut in early life. IMPORTANCE This study addresses the microbiology of a natural ecosystem (the infant bowel) for children in a rural setting in Indonesia and in an urban environment in New Zealand. Analysis of DNA sequences generated from the microbial community (microbiota) in the feces of the infants during the first year of life showed marked differences in the composition and complexity of the bacterial collections. The differences were most likely due to differences in the prevalence and duration of breastfeeding of infants in the two countries. These kinds of studies are essential for developing concepts of microbial ecology related to the influence of nutrition and environment on the development of the gut microbiota and for determining the long-term effects of microbiological events in early life on human health and well-being.